Meningkatkan Aktivitas Peserta Didik Dalam Pembelajaran Ppkn Melalui Whatsapp - Wijiana Wijiana (LPMP Provinsi DKI Jakarta, 2021)
Most students are not enthusiastic about participating in online learning. Therefore we need a way to activate students in learning through WhatsApp Groups. This research aims to determine the increase in students activity through WhatsApp in PPKN learning on basic competence analysis the forming process of Pancasila as fundament philosophy. The subject on this research is students of 87 Junior High School for the seventh grades. This research with 2 cycles. Each cycles consists of four stages, namely planning, implementing, acting, observing and reflecting. Data collection techniques carried out by monitoring during studying and taking test on the learners. In this research there are two research instruments, namely observation sheets and test. From the results, it is found out the learning outcome of learners knowleadge increased from 68% to 77% in cycle and cyclus II became 89%. It can be concluded that learning PPKN through WhatsApp can improve students activities